2007
DOI: 10.3382/ps.2007-00121
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Salmonella on Egg Conveyor Belts Is Dependent on the Belt Type but Not on the rdar Morphotype

Abstract: Commercial caged layer flocks in Alberta, Canada, are commonly monitored for Salmonella enterica serovar Enteritidis (SE) and S. enterica serovar Typhimurium (ST) by environmental sampling. In one recent case, a SE strain isolated from the egg conveyor belt was a source of persistent infection for the flock. This study was undertaken to examine Salmonella colonization on egg conveyor belts and to determine whether the rdar morphotype, a conserved physiology associated with aggregation and long-term survival, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…Development of lux-based reporters containing promoter regions cloned into a low-copy luciferase vector have been previously described for mlrA , agfD, agfB, adrA and s 70 (Stocki et al, 2007).…”
Section: Gene Expression Assaysmentioning
confidence: 99%
“…Development of lux-based reporters containing promoter regions cloned into a low-copy luciferase vector have been previously described for mlrA , agfD, agfB, adrA and s 70 (Stocki et al, 2007).…”
Section: Gene Expression Assaysmentioning
confidence: 99%
“…Another study on colonization and persistence of Salmonella on egg conveyor belts indicated that the type of egg belt (i.e. vinyl, nylon, hemp or plastic) was the most important factor in colonization and persistence, while rdar morphotype, a physiological adaptation associated with aggregation and long-term survival which is conserved in Salmonella , surprisingly, was not essential for persistence (Stocki et al, 2007). Interestingly, inoculation onto fresh-cut produce surfaces, as well as onto inert surfaces, such as polyethersufone membranes, was found to significantly increase the survival of salmonellae during otherwise lethal acid challenge (pH 3.0 for 2 hours) (Gawande & Bhagwat, 2002).…”
Section: Attachment To Food-contact Surfaces and Biofilm Forming Abilmentioning
confidence: 99%
“…For example, an S. Enteritidis strain isolated from an egg conveyor belt was found to be a source of persistent infection in poultry (Stocki et al, 2007). Similarly, Salmonella was able to persist in food bowls that had contained raw meat contaminated by this pathogen (Weese & Rousseau, 2006).…”
Section: Implication Of Biofilms In the Tolerance Response Of Salmonementioning
confidence: 99%